Minimally Invasive Cochlear Implantation: First-in-Man of Patient-Specific Positioning Jigs - Salcher, Rolf; John, Samuel; Stieghorst, Jan; Kluge, Marcel; Repp, Felix; Fröhlich, Max; Lenarz, Thomas (Frontiers in Neurology, 2022)
A minimally-invasive surgical (MIS) approach to cochlear implantation, if safe, practical, simple in surgical handling, and also affordable has the potential to replace the conventional surgical approaches. Our MIS approach uses patient-specific drilling templates (positioning jigs). While the most popular MIS approaches use robots, the robotic aspect is literally put aside, because our high-precision parallel kinematics is only used to individualize a positioning jig. This jig can then be mounted onto a bone-anchored mini-stereotactic frame at the patient’s skull and used to create a drill-hole through the temporal bone to the patient's cochlea. We present the first clinical experience where we use sham drill bits of different diameter instead of drilling into the bone in order to demonstrate the feasibility and accuracy.